Nepal Multidimensional Poverty Index: Analysis towards action - Oxford Poverty and Human Development Initiative (OPHI) (Government of Nepal National Planning Commission, 2021)
This report provides the first update to Nepal’s official national Multidimensional Poverty Index (MPI). While the first MPI used 2014 data from the Nepal Multiple Indicator Cluster Survey (NMICS), the updated MPI in this report uses 2019 data from the same NMICS report. In this report, minor adjustments were made to five indicators in 2021 in line with Nepal’s national policy aspirations and to align with the global MPI and Sustainable Development Goals (SDGs) to allow for ongoing international comparability. The five indicators were nutrition, child mortality, years of schooling, housing, and assets. The main findings using the previous definition are also transparently presented in the appendix. The results from both measures are similar in terms of the scope of poverty and patterns of its reduction. In 2019, 17.4 percent of Nepalis are multidimensionally poor – just under five million persons, and the MPI is 0.074. Across indicators, the highest number of people are deprived in housing materials, clean cooking fuel, years of schooling, assets, and nutrition. Considering the indicator weights, years of schooling and nutritional deprivations contribute most to ongoing multidimensional poverty in Nepal. Disparities exist: for example, 28 percent of rural dwellers are MPI poor, compared with 12.3 percent in urban areas (using the updated definitions of rural and urban zones), and over half of Nepal’s poor population live in rural areas. Across provinces, 39.5 percent of people in Karnali Province are MPI poor – by far the highest – followed by 25.3 percent in Sudurpashchim Province and 24.2 percent in Province 2. In contrast, in Gandaki Province 9.6 percent of people are multidimensionally poor, while this falls to 7.0 percent in Bagmati Province. However, Executive Summary in terms of number of poor, the largest number live in Province 2, followed by Lumbini Province and Province 1. Children are the poorest – 21.8 percent of children under 18 years of age are MPI poor compared with 15.1 percent of adults. Furthermore, 44 percent of poor people are children under the age of 18, making this group pivotally important for policy. And if the household includes a member with a disability, overall poverty rises to 18.3 percent, versus 17.4 percent otherwise.